1989
DOI: 10.1017/s0022029900026509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-lactoglobulin and κ-casein genetic variants and concentrations on syneresis of gels from renneted heated milk

Abstract: Milk protein genetic polymorphism has a major influence on the composition of milk, and on its processing properties, including yield of cheese (see Schaar et al. 1985;McLean et al. 1984McLean et al. , 1987McLean, 1987). However, there appears to be little information on the effects of milk protein genetic variants on syneresis of cheese curd. The effect of casein composition on syneresis was studied by Pearse el al. (1986), who found that syneresis was affected only by the level of /?-casein. Syneresis is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Milk protein genetic polymorphism has received considerable research interest in recent years because of possible associations between milk protein genotypes and economically important traits in dairy cattle. Many research reports have indicated that certain milk protein variants may be associated with milk production [ 1 - 4 ], milk composition [ 5 - 15 ] and cheese production [ 5 , 6 , 12 - 14 , 16 - 20 ]. Therefore, milk protein genes could be useful as genetic markers for additional selection criteria in dairy cattle breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Milk protein genetic polymorphism has received considerable research interest in recent years because of possible associations between milk protein genotypes and economically important traits in dairy cattle. Many research reports have indicated that certain milk protein variants may be associated with milk production [ 1 - 4 ], milk composition [ 5 - 15 ] and cheese production [ 5 , 6 , 12 - 14 , 16 - 20 ]. Therefore, milk protein genes could be useful as genetic markers for additional selection criteria in dairy cattle breeding.…”
Section: Introductionmentioning
confidence: 99%
“…This latter reaction appears to inhibit the renneting process, perhaps by occluding the site of hydrolysis in x-casein (van Hooydonk et al, 1987). The naturally occurring BLG variants found in bovine milk can affect a number of properties including cheese yield and syneresis (Marziali and Ng-Kwai-Hang, 1986;Pearse et al, 1985; McLean and Schaar, 1989; Sweetsur and White, 1974). Preliminary * Address correspondence to this author at 413 Stocking Hall, Cornell University, Ithaca, NY 14853 [telephone (607) 255-2896; fax (607) 255-8741].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of whey separation by the addition of BLG however, reached a maximum when the concentration of BLG added was equivalent to that normally in milk. 18 ) In our studies, the addition of milk solids and small quantities of BLG decreased the whey separation of set-type yogurt produced with milk which was preheated at 85°C for 30 min. The reduction in whey confirmed the benefits of adding BLG to this type of product (Table).…”
Section: Discussionmentioning
confidence: 46%